Structural and functional characterization of genes related to the quality of plant products in olive (Olea europaea L.) - Iaria,Domenico Lorenzo; Bitonti,Maria Beatrice; Iorio,Gabriele (My University, 2013)
Background. Olive (Olea europaea L.) is an emblematic species and one of the most widespread fruit tree in the Mediterranean basin. It is a member of the Oleaceae family, which includes 600 species within 25 genera distributed over all continents, from northern temperate to southern subtropical regions and from low to high altitudes. On the basis of several morphological synapomorphies, Oleaceae family is considered as monophyletic and is easily circumscribed. Within the family, phylogenetic relationships among genera have been assessed by a cladistic analysis of chloroplast non-coding DNA sequences. The different members of Oleaceae family are trees, shrubs or woody climbers and among them Olea europaea L. features as an evergreen schlerophyllous tree. Native to the Mediterranean region, olive represents a unique species within the Olea genus that produces edible fruits. There are historical evidences that the utilization of wild olive as fruit tree can be dated to Neolithic period, as early as the 8th millennium B.C., and that its domestic cultivation was firstly undertaken on Crete island during the Minoan period, between 1500–3000 BC. From here, olive plants and their products were exported not only towards mainland Greece, but also to Northern Africa and Asia Minor. Today, olive is one of the most extensively cultivated crop species in the world and about 96% of olive cultivated area is within the Mediterranean basin (8,6 million of hectares, over 750 million of trees). Most of olive fruits is destined for oil production. About 73 % of the global oil production comes from European Countries and main producers among them are Spain, Italy and Greece. However, a considerable part of olive fruits is destined for direct human consumption as table olives, whose worldwide production amounts to about 17 million tons. Primarily, the quality of olive products (e.g. table olive and oil) relies on agronomic and organoleptic features of fruits which according to botanical nomenclature are named “drupes”. On the other hand the distinctive features of drupe vary in relation to the genetic traits (cultivar) but also to ripening stage as well as to the environmental growth conditions (i.e. soil and climatic conditions). Note that, these latter potentially include different biotic and abiotic stressful factors that, besides influencing plant productivity, strongly impact on the quality of its product. Commonly, a “good” oil (i.e. obtained from healthy drupes collected at the optimal maturation stage) contains about 98% of acyl lipids while the remaining 2% includes several minor component such as polyphenols, esters, terpenes, chrorophyll, tocopherols, phylloquinones, vitamin K and unsaponifiable volatiles. The monounsaturated oleic acid represents the main component of lipidic fraction (up to 80%). Other major fatty acids are the polyunsaturated linoleic acid (2.5–20%) and the saturated palmitic acid (10–20%). Certainly, a strong impact on the perception of olive oil quality is played by sensory testing which in turn is tightly related, on one hand to a well-balanced composition of fatty acids and, on the other, to the profile of minor components. Chief among these components are different volatiles responsible for characteristic aroma which make olive products unique among other oils. Moreover, olive oil quality strongly relies on the presence of antioxidant compounds, such as polyphenols and tocopherols, which ensures the stability of fatty acids, acting as an effective scavenging system of reactive oxygen radicals and thus largely reducing lipid peroxidation. Taking into account the above features it is clear that oil extraction process is rather relevant for preserving oil sensory properties and a high oxidative stability during storage . So far, olive oil is the only major dietary oil extracted by pressing rather than by solvent extraction. Therefore, no harsh treatment (high temperature, organic solvents and removal of these by evaporation) is generally applied before olive oil is ready for human consumption. This allows olive oil to maintain the integrity of its minor constituents, such as polyphenols, tocopherols and volatile compounds, which are partly water-soluble and, as above mentioned, play a key role in conferring oxidative stability and sensory properties. It is worth noting that olive oil is a predominant and relevant component of so-called “Mediterranean diet”. To day, a major attention is worldwide paid to this diet as a result of the even increasing evidences of its protective action against cardiovascular diseases and cancer, derived by both fundamental researches and epidemiological studies. Concerning olive oil, healthy property is related to the above mentioned high proportion of monounsaturated fats as well as to the high content of antioxidants (i.e. phenols, tocopherols, phylloquinones, vitamin K) (Green, 2002). Consistently with this role, worldwide consumption of olive oil multiplied 6-fold over the past 30 years. Despite the relevant properties of olive plant products, breeding strategies for this crop species are still long term due to the long juvenile phase before flowering (20/25 years) and the inherent self-incompatibility. Currently, olive germoplasm is under an intensive survey but its characterisation is far from a clear definition, even though it has recently benefited by the availability of genomic polymorphic markers. Very recently, pyrosequencing technology provided large scale information on the structure and putative function of gene transcripts in relation to drupe development. Notwithstanding, the information on the genetic control underlying specific agronomic traits and/or physiological performance of olive plant is still limited. Hence, fundamental and applied research is required to improve olive breeding programs. In particular, a wider characterization of genes related to both the quality of plant products and the adaptive mechanism to abiotic and biotic stresses could provide knowledge and tools for marker aided selection (MAS) and biotechnological approach, as well as for developing appropriate farming techniques leading to enhance productivity and quality of this unique oil tree species.
Dottorato di ricerca in Ambiente Salute e Processi Ecosostenibili, XXIII CICLO, a.a.2007-2010
Keywords: Biologia vegetale; Piante oleifere; Olea europea